2018
DOI: 10.1111/jzo.12578
|View full text |Cite
|
Sign up to set email alerts
|

Overmarking by adult females in four equid species: social bonds and group cohesion

Abstract: Scent marking by overmarking deposits made by conspecifics has been well studied in male mammals, but this phenomenon remains poorly understood and rarely studied in females. Furthermore, in socially living mammals like most ungulate species many of the established hypotheses cannot be applied, leaving the function of female overmarking unexplained. In this study, we suggest and test a novel hypothesis: maintenance of social bonds. We examined the occurrence of adult female overmarking in equids and test three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…We found that gazelles visited scent-marking stations closer to visitors' infrastructure less frequently. Scent-marking stations serve not only for male territorial marking (Gosling, 1982;Wronski et al, 2013;Yom-Tov, 2016) but also as communication centres between individuals in the population (Johnson, 1973;Tučková et al, 2018;Wronski et al, 2013). Tučková et al (2018) showed that frequent visits to scent-marking stations improved bonds and group cohesion in different species of equids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that gazelles visited scent-marking stations closer to visitors' infrastructure less frequently. Scent-marking stations serve not only for male territorial marking (Gosling, 1982;Wronski et al, 2013;Yom-Tov, 2016) but also as communication centres between individuals in the population (Johnson, 1973;Tučková et al, 2018;Wronski et al, 2013). Tučková et al (2018) showed that frequent visits to scent-marking stations improved bonds and group cohesion in different species of equids.…”
Section: Discussionmentioning
confidence: 99%
“…Scent-marking stations serve not only for male territorial marking (Gosling, 1982;Wronski et al, 2013;Yom-Tov, 2016) but also as communication centres between individuals in the population (Johnson, 1973;Tučková et al, 2018;Wronski et al, 2013). Tučková et al (2018) showed that frequent visits to scent-marking stations improved bonds and group cohesion in different species of equids. Sociality in females is linked to reproduction success (Cameron et al, 2009;Silk et al, 2003), reduces aggression and stress (Stanley & Dunbar, 2013) and thus increases fitness.…”
Section: Discussionmentioning
confidence: 99%